A Comparative Study about the Use of Artificial Intelligence (AI) in Public Administration of Nordic States with other European Economic Sectors - Butt, Junaid Sattar (EuroEconomica, 2024)
Artificial Intelligence (AI) is revolutionizing public administration in Nordic countries like Denmark, Finland, Iceland, Norway, and Sweden. This integration of AI technologies is transforming governance practices, improving efficiency, service quality, and citizen engagement. The European Union tracks and quantifies the digitization of public and fiscal administration using the Digital Economy and Society Index (DESI) index, indicating the level of digitization at the European level. The study explores the use of AI in Nordic states, focusing on strategies and integration of AI technologies in service delivery processes. It examines the region’s strong digital infrastructure, emphasis on responsible data use, and high public trust in government. The research reviews policies, strategies, and case studies to understand the drivers, challenges, and outcomes of AI deployment in various administrative domains. It also compares the use of AI in Nordic Public Administration with other European Economic Sectors, identifying lessons learned and best practices for future implementation. The study aims to identify strengths and potential challenges for Nordic states in enhancing efficiency, transparency, and citizen engagement. The findings contribute to both scholarly discourse and practical policymaking by offering insights into the opportunities and challenges associated with AI adoption in Nordic public administration and further underscores the importance of fostering interdisciplinary collaboration, knowledge exchange, and international partnerships to maximize the benefits of AI while addressing concerns about fairness, equity, and societal impact. Ultimately, this research contributes to a deeper understanding of the evolving role of AI in shaping the future of governance and public service delivery in the Nordic region.